Bullying on Social Media: Primitive Behavior Against Prophetic Marchals From A Hadith Ahkam Perspective - Ahmad, La Ode Ismail; Ali, Muhammad; Mirwan, Mirwan; Sakka, Abdul Rahman; Mosiba, Risna (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2024)
This article aims to outline some prophetic instructions regarding social interaction to avoid bullying behavior. This study uses a normative qualitative method, namely analyzing hadiths related to bullying with an ahkam hadith perspective.  This study concludes that bullying behavior from the perspective of hadith is: 1) The Hadith narrated by Ibn Majah generally explains how the Prophet's Hadith views bullying as leading to degrading behavior. This is obtained from the word ihtiqarwhich has a correlation in meaning with the orientation of bullying behavior itself, namely degrading. Then a complete reading of the hadith narrated by Imam Muslim adds an explanation of indications of bullying behavior such as envy, hatred, belittling and tyrannizing other people. These attitudes are the seeds of hostility and division between people; 2) The basic idea of Ibn Majah's hadith number 3203 is the value of humanism, namely the effort to maintain a humane attitude towards fellow humans in any situation and condition. In the previous comprehensive thematic study, it was also sufficient to contribute to the conclusion of the basic idea of the hadith studied, namely explaining the consequences for perpetrators of bullying both verbally and physically. This spirit is in line with the spirit of humanism which condemns all kinds of acts of harassment or degrading towards fellow human beings. Therefore, in the perspective of ahkam hadith there is a need for preventive measures in order to prevent or overcome this act of bullying; 3) The preventive measures offered by this hadith are: a) providing spiritual awareness of the importance of preventing bullying early, b) supporting cooperation and breaking the cycle of conflict, c) eliminating inferiority for victims of bullying and honing assertive skills.